Social (Im)mobility in Low-skilled and Low-wage Immigrant Niches - Slettebak, Marie Holm; Rye, Johan Fredrik (Nordic Journal of Working Life Studies, 2022)
In the last two decades, many labor migrants have arrived in the Nordic countries where they concentrate in certain low-wage and low-skilled jobs – immigrant niches. The article analyzes the scope of social (im)mobility in terms of occupational careers, income change, and job stability for native and foreign-born workers in immigrant niches in the low-skilled and low-wage section of the labor market. The case study is Norway’s fish processing industry, where labor immigrants from Central and Eastern Europe have largely replaced Norwegian-born workers in manual jobs since 2004 and now dominate the workplace alongside a smaller number of non-Western immigrant workers. The article uses full population register data (n = 4164, Microdata.no) to analyze differences in workers’ social trajectories between 2009 and 2018. Results show significant variation between workers: Norwegian-born (non-immigrant) workers appear to have greater upward social mobility than EU11 immigrant workers, who in turn do better than non-Western immigrant workers.